BASIC DETERMINANTS OF EFFECTIVE HEALTH INSTITUTIONS MANAGEMENT AS AN ELEMENT OF SOCIAL AND MEDICAL PROVISION IN A REGION - Кобушко, Я.В.; Летуновська, Н.Є.; Христій, В.Ю. (Управління змінами та інновації, 2022)
The research subject is the socio-economic relations system that takes place in the management system of health care institutions. The article aims to identify directions for increasing the efficiency of management of health care facilities. A comparative analysis of existing approaches to managing medical facilities was carried out. Conclusions were made that the national health care system of Ukraine, needs adaptation to modern technologies and socio-economic changes caused by the emergence of epidemiological threats such as COVID-19. The authors determined the peculiarities of the functioning of the medical services market. Specific characteristics for the market of medical services and unique accents in the state regulation of this market are revealed. The health care system of another country is briefly analyzed with an emphasis on innovative components. Based on the research results, proposals are given for implementing measures to improve the management of health care institutions.